The updated PIM-Taiwan criteria: a list of potentially inappropriate medications in older people. (October 2019) - Chang, Chirn-Bin; Lai, Hsiu-Yun; Hwang, Shinn-Jang; Yang, Shu-Yu; Wu, Ru-Shu; Chang, Lo-Yu; Lee, I-Shan; Liu, Hsing-Cheng; Chan, Ding-Cheng
Background: Explicit criteria for potentially inappropriate medications (PIMs) developed for other countries are difficult to apply to a specific territory. This study aimed to update the PIM-Taiwan criteria from a qualitative review of several published PIM criteria, followed by consensus among regional experts in Taiwan. Methods: After a review of the literature, we selected four sets of published PIM criteria to construct preliminary core PIMs. The Beers criteria, Fit fOR The Aged (FORTA), and Japan criteria were used for PIMs, without consideration of chronic diseases. The Beers criteria, Screening Tool of Older Persons' Prescriptions (STOPP) criteria, and Japan criteria were used for PIMs with respect to chronic diseases. We asked experts ( n = 24) to rate their agreement with each statement, including in the final PIM criteria, after two rounds of modified Delphi methods. The intraclass coefficient (ICC) was used to examine the reliability of the modified Delphi method. Results: Overall, two categories of PIMs were established: 131 individual drugs and 9 drugs with combinations that should generally be avoided; and 9 chronic diseases with their corresponding PIMs that have drug–disease interactions. The ICC estimates for PIMs to be avoided generally were 0.634 and 0.557 (round 1 and 2) and those for PIMs with respect to chronic diseases were 0.866 and 0.775 (round 1 and 2) of the Delphi method, respectively. Conclusions: The 2018 version of PIM-Taiwan criteria was established and several modifications were made to keep the criteria updated and relevant. Clinicians can use them to reduce polypharmacy and PIMs among older patients.